Being on the mat: a process evaluation of trauma-informed yoga for women with substance use disorders - Smoyer, Amy (The Journal of Sociology & Social Welfare, 2016)
Yoga practice is associated with positive health outcomes, including benefits related to managing substance use disorders and trauma symptomology. However, low-income vulnerable communities have limited access to yoga. This process evaluation of a trauma-informed yoga program for women with substance use disorders demonstrates the feasibility and utility of using noncertified yoga instructors to offer a basic yoga in community-based agencies. Participants describe outcomes related to relaxation, mindfulness, and movement that are well-aligned with their recovery needs. Study findings suggest the utilization of instructors with minimal training has the potential to expand research about and access to yoga among marginalized communities. © 2016, Western Michigan University. All rights reserved.
Keywords: Evaluation; Qualitative; Substance use; Women; Yoga; dept.swk; ⛔ No DOI found

Food in correctional facilities: A scoping review - Smoyer, Amy B. (Appetite, 2019)
In the last 20 years, there has been an exponential increase in research about food in prison. Given this growing interest, it is appropriate to take stock of the field by mapping and synthesizing existing knowledge in order to identify gaps in knowledge and make recommendations for future research. Specifically, the purpose of this scoping review is to understand the experiences of incarcerated people with food in order to inform interventions that will promote positive outcomes for justice-involved individuals and correctional facilities. This review identified 38 peer-reviewed research articles about food in correctional facilities. This sample included qualitative (n = 28) and quantitative (n = 10) research that explored the both the pragmatic and symbolic dimensions of food in these settings. Taken together, this body of research provides a rich description of prison food practices and the implications of these practices on medical, psychological, and sociological outcomes. Moving forward, collaboration between academics, incarcerated people, and correctional practitioners is encouraged in order to develop programs that use this research to improve individual and intuitional outcomes. In addition, while emerging research has begun to develop knowledge about prison food in developing countries, the literature focuses primarily on the US, Canada and Western Europe and there is a need to expand the geographic scope of this inquiry.
19 citations (Crossref) [2023-10-31] Place: England Smoyer, Amy B. Department of Social Work, Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, USA. Electronic address: smoyera1@southernct.edu.
Keywords: *Food Services; *Prisons; Canada; Consumer Behavior; Europe; Food Services; Humans; Nutritive Value; Prisons; United States; Western Europe; adult; article; catering service; clinical article; consumer attitude; dept.swk; developing country; female; human; justice; male; nutritional value; peer-reviewed; physician; prison

Teaching note—Taking social work undergraduates inside: the inside-out prison exchange program - Smoyer, Amy B. (Journal of Social Work Education, 2020)
The Inside-Out Prison Exchange Program is an experiential learning program that involves teaching college courses inside correctional facilitates to classes that include incarcerated and nonincarcerated students. This teaching note describes the program and argues that its congruence with social work values makes it a valuable tool for preparing students to take on social justice work. The impact of the program’s pedagogy and structure on students’ and faculty’s capacity for critical thinking and self-reflection is described. Logistical issues to consider in developing programs are discussed.
0 citations (Crossref) [2023-10-31] tex.ids: smoyerTeachingNoteTaking2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85071417485 type: Article
Keywords: article; critical thinking; dept.swk; human; human experiment; pedagogics; peer-reviewed; prison; program impact; social work; teaching

“It's the black girls that have the most”: foodways narratives and the construction of race in a women's prison - Smoyer, Amy B (Food and Foodways, 2015)
Prison foodways narratives can expand knowledge about cultural beliefs and perceptions of correctional systems. This exploratory analysis, based in qualitative interview data, seeks to initiate dialogue about the ways in which formerly incarcerated women in the US deploy racialized food narratives when describing the acquisition, preparation, and consumption of prison food. The participants’ food narratives construct prison as a non-white space that is better matched for African-American and Latina women, reinforcing and enacting larger cultural notions about incarceration. This opening analysis calls for more research and deliberation about how prison foodways narratives contribute to understandings about and perceptions of correctional systems and incarcerated people. © 2015, Taylor & Francis Group, LLC.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-302-356-756-556 tex.type: [object Object]
Keywords: dept.swk

Making fatty girl cakes: food and resistance in a women's prison - Smoyer, Amy B. (The Prison Journal, 2016)
This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cellsall to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the rehabilitative potential of correctional facilities.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/095-837-797-757-693 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; food; prisoners; resistance; women

Feeding relationships: foodways and social networks in a women’s prison - Smoyer, Amy B. (Affilia, 2014)
Research has demonstrated the importance of supportive relationships and social networks to prisoners’ psychosocial outcomes, especially for women. Understandin...
25 citations (Crossref) [2023-10-31] Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: dept.swk; peer-reviewed

Book Review: Invisible Mothers: Unseen Yet Hypervisible After Incarceration by Garcia-Hallett, J. - Smoyer, Amy B. (Affilia, 2023)
Num Pages: 1
Keywords: book.review; dept.swk

Book Review: Mothering and desistance in re-entry - Smoyer, Amy B. (Affilia, 2020)
Keywords: book.review; dept.swk

Book Review: Refusal to Eat: A Century of Prison Hunger Strikes - Smoyer, Amy B. (Punishment & Society, 2023)
Keywords: book.review; dept.swk

Impact of Changes in Criminal-Legal Practices During the COVID-19 Pandemic on the HIV Risk Behaviors of Women Who Use Drugs: Protocol for a Multimethods Qualitative Study - Smoyer, Amy B. (JMIR Research Protocols, 2024)
Background: HIV risk behavior in women who use drugs is related to myriad psychosocial issues, including incarceration. The experience of incarceration elevates women’s HIV risk by disrupting social networks, housing, employment, and access to health care. During the COVID-19 pandemic, changes in criminal-legal practices resulted in decreased incarceration, especially among women. These changes may have largely altered HIV risk among women who use drugs, depending on their access to care in the community. Objective: This study seeks to build knowledge about the impact of shifts in criminal-legal practices during the COVID-19 pandemic on HIV risk behaviors of justice-involved women who use drugs. Methods: Qualitative methods are used to gather and analyze women’s narratives about their life experiences before and during the COVID-19 pandemic, with a focus on individual and structural determinants of HIV risk behaviors. Thirty formerly incarcerated women with a history of substance use are being recruited through collaboration with community partners. Each participant completes a sociodemographic survey and two interviews. The first interview uses a life history instrument that invites participants to reflect on key turning points in their lives. The second interview uses a calendar approach to gather information about participants’ lives during the first year of the COVID-19 pandemic (March 2020-March 2021). The interviews (1 hour each) are audio-recorded and transcribed for analysis. Rapid Qualitative Inquiry and thematic analysis are being used to manage, organize, and interpret the data. The study team will collaborate with a subset of participants to develop digital stories about their COVID-19 experiences, a process that allows for member-checking and triangulation. Findings will be disseminated to program and policy makers in academic venues, community settings, and social service agencies. Results: To date, 10 women’s data have been collected. In total, two themes have been identified in this preliminary data: (1)the chaos and instability of participants’ lives increased during the COVID-19 pandemic: participants reported a wide range of psychosocial and health problems and limited engagement with social service systems. Interaction with criminal-legal systems was rife with uncertainty; participants described living in a state of limbo, which was extremely stressful. (2) When asked to describe a “turning point” in their lives, many participants attributed their substance use to the traumatic loss of a child due to death, incarceration, or termination of parental rights. During the COVID-19 pandemic, participants’ struggles to cope with these unresolved experiences of grief and loss were intensified by the widespread death and dying of the pandemic. Conclusions: Preliminary findings suggest that HIV risk factors increased for participants during the COVID-19 pandemic and invite further investment in community-based harm reduction programs, especially housing, that support women who use drugs. Interventions that address experiences of maternal grief and loss may reduce women’s substance use. Trial Registration:
Company: JMIR Research Protocols Distributor: JMIR Research Protocols Institution: JMIR Research Protocols Label: JMIR Research Protocols
Keywords: dept.swk; peer-reviewed

Hungry on the inside: Prison food as concrete and symbolic punishment in a women’s prison - Smoyer, Amy B; Lopes, Giza (Punishment & Society, 2017)
Women’s perceptions of the prison experience and the punishing dimensions of their confinement are under-examined. To expand knowledge in this area, Sexton’s theory of penal consciousness is used to analyze formerly incarcerated women’s narratives about prison food. This analysis builds understanding about the lived experience of incarceration by explicating one dimension of prisoners’ understandings and perceptions of punishment. Women’s narratives describe both concrete and symbolic punishments associated with food. Participants spoke about poorly designed, sloppy food systems that left them feeling uncared for, ignored, frustrated, and humiliated. Women articulate experiences of hunger that reflect both a deprivation of adequate food and a rationing of humane attentions. These punishing perceptions may inhibit the efforts of social service and health providers to engage incarcerated and formerly incarcerated women in care. In contrast, exceptional participant narratives about positive, non-punishing food experiences suggest that ameliorated food systems could improve the lived experience of incarceration and promote the engagement in services that is needed to improve the outcomes of incarcerated and formerly incarcerated women.
54 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000395402500006, lens.org/015-306-581-234-40X tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; food; prison; punishment; women

The everything else - Smoyer, Amy B. (Sensory Penalities, 2021)
Sensory Penalties aims to reinvigorate a conversation about the role of sensory experience in empirical investigation. It explores the visceral, personal reflections buried within forgotten criminological field notes, to ask what privileging these sensorial experiences does for how we understand and research spaces of punishment and social control.
Keywords: dept.swk

Dealing food: Female drug users’ narratives about food in a prison place and implications for their health - Smoyer, Amy B.; Blankenship, Kim M. (International Journal of Drug Policy, 2014)
18 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Food systems in correctional settings: a literature review and case study - Smoyer, Amy B.; Kjær Minke, Linda (World Health Organization. Regional Office for Europe, 2015)
Food is a central component of life in correctional institutions and plays a critical role in the physical and mental health of incarcerated people and the construction of prisoners’ identities and relationships. An understanding of the role of food in correctional settings and effective management of food systems may improve outcomes for incarcerated people and help correctional administrators to maximize the health and safety of individuals in these institutions. This report summarizes existing research about food systems in correctional settings and provides examples of food programmes in prison and remand facilities, including a case study of food-related innovation in the Danish correctional system. Specific conclusions are offered for policy-makers, administrators of correctional institutions and prison food services professionals,and ideas for future research are proposed.
Accepted: 2019-08-13T14:39:22Z
Keywords: dept.swk

Hope, courage, and resilience in the lives of transgender women of color - Ruff, Nadine; Smoyer, Amy; Breny, Jean (The Qualitative Report, 2019)
There is a lack of qualitative and strengths-based knowledge about the lived experience of transgender women of color in the US. To address this research gap, a Photovoice project was undertaken with five transgender women living in a small urban area. Thematic analysis of the participants' discussion of their photographs identified three major themes: Hope, courage, and resilience. Analysis suggests a framework for understanding these women's lived experiences and the psychosocial tools that they use to negotiate their daily lives and persevere in the face of interpersonal and structural oppression. © 2019 Nova Southeastern University. All rights reserved.
2 citations (Crossref) [2023-10-31] tex.ids: ruffHopeCourageResilience2019a
Keywords: Courage; Hope; Photovoice; Resilience; Transgender Women; Women of Color; dept.pch; dept.swk; peer-reviewed; ⛔ No DOI found

Self-Concept Among Formerly Incarcerated Sexual Minority Women - Stone, Al; Smoyer, Amy; D’Angelo, Karen (Social Sciences, 2025)
Sexual minority women (SMW) are a resilient yet vulnerable population who may experience poor psychosocial outcomes due to minority stress associated with their marginalized status and traumatic experiences resulting from interpersonal and structural violence. When SMW are incarcerated, the trauma of this experience can exacerbate existing mental health challenges. Self-concept is a key measure of mental health that is associated with increased self-efficacy and positive psychosocial outcomes. This analysis explores the ways in which incarceration impacts the self-concept of SMW. Secondary data analysis of three qualitative interviews with formerly incarcerated SMW was conducted. Specifically, Gilligan’s Listening Guide was used to create “I poems” that articulate the participants’ narratives and contrapuntal voices. These poems were then analyzed to build knowledge about participants’ self-concept. This analysis informs our understandings of self-concept among SMW, violence against women, the vulnerability of binary constructs, and the ways in which people negotiate past, present and future selves. The findings can inform interventions that seek to mitigate the psychosocial risks faced by SMW and formerly incarcerated people and improve outcomes for these populations.
Keywords: Clinical psychology; Developmental psychology; LGBT; Listening Guide; Psychology; Sexual minority; Sexual orientation; Social psychology; dept.swk; incarceration; lesbian; qualitative; self-concept; sexual minority women; transgender

Prison food in Denmark: Normal responsibility or ethnocentric imaginations? - Minke, Linda Kjær; Smoyer, Amy B. (Scandinavian penal history, culture and prison practice - Embraced by the welfare state?, 2017)
This book draws on historical and cross-disciplinary studies to critically examine penal practices in Scandinavia. The Nordic countries are often hailed by international observers as ‘model societies’, with egalitarian welfare policies, low rates of poverty, humane social policies and human rights...
Citation Key Alias: lens.org/077-884-123-268-809, minkePrisonFoodDenmark2017a
Keywords: dept.swk

Masculine embodiment among sexual minorities in a women’s prison - Smoyer, Amy B.; Divita, David; Perrault, Allison (Australian Social Work, 2021)
Sexual minority women are disproportionately incarcerated and more likely to experience structural and interpersonal violence while incarcerated than heterosexual cisgender women. To build knowledge about this population and inform social work practice, theories of embodiment were used to conduct thematic analysis of five interviews with lesbian, gay, bisexual, transgender, and queer masculine-identified people who had been incarcerated in a women’s prison. This analysis explicates how participants used bodily practices to construct gender and communicate identity to themselves and others. Uniforms, prison regulations, and physical manifestations of female embodiment complicated these efforts. Participants described the ways in which they monitored and evaluated their own bodies while also managing the constant surveillance of their bodies by others. Taken together, these findings explicate the ways in which participants’ bodies were produced both through their actions and the external gaze of others. Implications for social work include exploration of language and masculinity in practice settings and suggestions for correctional policies. Findings encourage inclusion of non-binary frameworks and increased attention to the embodied self in order to expand understandings of human behaviour in the social environment. IMPLICATIONS Interpret with caution any information about gender identity surmised from intake forms and observation of clients’ bodily practices. Ask clients to describe their gender identity. Prioritise correctional policies that promote the health and safety of incarcerated people and staff over policies that enforce social norms related to gender and have no implications on security. Encourage re-entry service providers to collaborate with LGBTIQA+ organisations that provide social support to clients who identify as sexual minorities. © 2021 Australian Association of Social Workers.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101127893
Keywords: LGBTQIA+ people; adult; article; attention; correctional facility; dept.swk; female; gaze; gender identity; human; interview; language; male; masculinity; organization; peer-reviewed; security; social environment; social norm; social support; social work practice; thematic analysis

Humans peeing: Justice-involved women’s access to toilets in public spaces - Smoyer, Amy B.; Pittman, Adam; Borzillo, Peter (PLOS ONE, 2023)
Justice-involved women face myriad challenges as they negotiate the terms of community supervision and manage the long-term implications and stigma of living with a criminal record. Major tasks that women juggle include securing safe, affordable housing, finding and retaining employment, accessing physical and mental health care (including substance use treatment), and handling relationships with family, friends, children, and intimate partners. In addition to these responsibilities, women must meet their basic physiological needs to eat, sleep, and use the toilet. Women’s ability to safely meet their personal care needs may impact their capacity to manage their criminal-legal challenges. This study uses qualitative methods to understand justice-involved women’s lived experiences related to urination. Specifically, the study reports on a thematic analysis of 8 focus groups conducted with justice-involved women (n = 58) and the results of a toilet audit conducted in the downtown areas of the small city in the United States where the focus group participants were living. Findings suggest that women had limited access to restrooms and reported urinating outside. Lack of restroom access impacted their engagement with social services support and employment and their ability to travel through public spaces. Women perceived their public toilet options as unsafe, increasing their sense of vulnerability and reinforcing the idea that they did not have full access to citizenship in the community because of their criminal-legal involvement. The exclusion and denial of women’s humanity that is perpetuated by a lack of public toilet access impacts women’s psychosocial outcomes. City governments, social service agencies, and employers are encouraged to consider how lack of toilet access may impact their public safety and criminal-legal objectives and expand opportunities for people to access safe restroom facilities.
1 citations (Crossref) [2023-10-31]
Keywords: Bladder; Employment; Jobs; Mental health and psychiatry; Prisons; Sexual and gender issues; Urban areas; Urination; dept.swk; peer-reviewed

Setting the stage: creating study sites that promote the safety and dignity of research participants - Smoyer, Amy B.; Rosenberg, Alana; Blankenship, Kim M. (Social Work Research, 2014)
The U.S. Department of Health and Human Services' (HHS) Code of Federal Regulations regarding Protection of Human Subjects (45 C.F.R. part 46) provides guidance
1 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Stigma, housing and identity after prison. - Keene, Danya E; Smoyer, Amy B; Blankenship, Kim M (The Sociological review, 2018)
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.
54 citations (Crossref) [2023-10-31] Place: England Keene, Danya E. Yale School of Public Health, USA. Smoyer, Amy B. Southern Connecticut State University, USA. Blankenship, Kim M. American University, Washington, DC, USA.
Keywords: Housing; Incarceration; Spatial stigma; dept.swk; peer-reviewed

Older adults’ lived experience of incarceration - Smoyer, Amy B.; Madera, Johanna Elumn; Blankenship, Kim M. (Journal of Offender Rehabilitation, 2019)
This qualitative analysis explores older adults’ lived experiences of incarceration. As part of a larger mixed-methods longitudinal study, 23 older adults were interviewed about their prison and reentry experiences. Findings describe experiences of loss, lack of medical attention, abuse by staff and other inmates, and the uncertainties and danger of prison life. After release, participants reported experiencing anxiety and stress related to their prison experiences. While participants reported that the ability to manage prison life deteriorated with age, some benefits of their senior status were also described. Maturity may allow older prisoners to remove themselves from volatile situations. Participants described experiences of rest and recovery, reflecting coping mechanism and resilience that could improve psychosocial outcomes during and after prison. This descriptive analysis centers the voices of older prisoners and informs interventions to support this vulnerable community.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-126-745-669-828, pop00096 tex.type: [object Object]
Keywords: Prison; dept.swk; incarceration; older people; peer-reviewed; qualitative; reentry

Lessons learned from COVID-19: Being known in online social work classrooms - Smoyer, Amy B; O’Brien, Kyle; Rodriguez-Keyes, Elizabeth (International Social Work, 2020)
This article presents findings from a survey of undergraduate social work (Bachelor of Social Work [BSW]) students about their experiences with remote learning during the 2020 COVID-19 pandemic. In response to this crisis, remote learning was rapidly implemented and many BSW educators and students experienced online classrooms for the first time. Findings from this study shed light on how remote learning shapes the interpersonal relationships and communication that are so critical to building students’ sense of classroom belonging, engagement, and learning.
Keywords: dept.hls; dept.rec; dept.swk; peer-reviewed

Negotiating toilet access: a qualitative exploration of women's incarceration - Smoyer, Amy B.; Schwarz, Paige; Camenga, Deepa; Rickey, Leslie (The Prison Journal, 2023)
Norms and behaviors about toileting in prison can expand understanding of women's lived experience of incarceration. Knowledge about this subject is significant because access to clean, safe toilets is a human rights issue, and toilet habits can impact social, mental, and physical outcomes. Three focus groups were conducted with 15 incarcerated women about their quotidian prison toilet experiences. While the toilet was physically available, institutional regulations, social norms, and women's individual psychologies limited their access and utilization. The ways in which toilet use was negotiated with self, peers, and are described, and the implications of these findings are discussed.
0 citations (Crossref) [2023-10-31]
Keywords: dept.swk; peer-reviewed

Ping-pong housing: Women’s post-incarceration trajectories - Smoyer, Amy B; Keene, Danya E; Oyola, M.; Hampton, A (Affilia, 2020)
This study examines the post-incarceration housing experiences of 33 women. Using Residential Timeline Followback methodology, participants were asked to report where they lived at arrest and every location since their release. Follow-up questions asked women to describe these locations, who they lived with, how much they paid, and whether or not they felt safe. Demographic information and criminal justice history were recorded. The data paint a complicated picture of social and community resources, persistence, and struggle. Housing assets lost at incarceration were difficult to recover. Most women bounced between various locations, relying heavily on short-term subsidized congregate housing programs and rarely securing independent housing. Participants described the family, friends, and acquaintances who housed them during reentry as overextended and vulnerable. Implications for policy and practice are explored. © The Author(s) 2020.
2 citations (Crossref) [2023-10-31] tex.ids: smoyerPingpongHousingWomen2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85090556112 type: Article
Keywords: dept.swk; peer-reviewed

Healthcare-induced trauma in correctional facilities: a qualitative exploration. - Elumn, Johanna; Keating, Layne; Smoyer, Amy B.; Wang, Emily A. (Health & justice, 2021)
Background: While incarcerated people are known to experience trauma at higher rates than the general population, little is known about how the correctional health system contributes to trauma rates. Methods: We conducted 20 semi-structured qualitative interviews with men who were recently released from a correctional system to understand their experiences with healthcare systems and medical staff during incarceration. Using reflexive thematic analysis within a critical realist framework, we coded and analyzed the data iteratively to refine and unify emerging themes. Results: The unanticipated concept of healthcare-induced trauma emerged and was revealed in three overall themes: (1) healthcare leading to fear of serious illness or death, (2) healthcare leading to fear of people, including healthcare providers, correctional staff, and other incarcerated people, and (3) the correctional institutional, social, and physical environment leads to fear of place. Conclusions: Healthcare in correctional settings has the potential to induce trauma, even when the medical conditions addressed are not life-threatening. Future research should examine the factors contributing to the development of healthcare-induced trauma in correctional settings and develop interventions to prevent and address this phenomenon. © 2021, The Author(s).
4 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8215321 ; https://link.springer.com/content/pdf/10.1186/s40352-021-00139-5.pdf ; https://europepmc.org/article/MED/34152487 ; https://healthandjusticejournal.biomedcentral.com/articles/10.1186/s40352-021-00139-5 ; https://www.scilit.net/article/383f51dcc8196ed4f25343a7df3d3b1b?action=show-references ; https://www.ncbi.nlm.nih.gov/pubmed/34152487
Keywords: dept.swk; peer-reviewed

Stress, Marginalization, and Disruption: A Qualitative Rapid Situational Assessment of Substance Users and HIV Risk in Lebanon - Khoshnood, Kaveh; Smoyer, Amy B.; Maviglia, Francesca; Kara, Janine; Khouri, Danielle; Fouad, Fouad M.; Heimer, Robert (International Journal of Environmental Research and Public Health, 2022)
Lebanon is a diverse and dynamic nation of six million people that has experienced considerable disruption for the last two decades. The Syrian Civil War, which began in 2011, resulted in the displacement of 1.1 million Syrians to Lebanon. Today, Lebanon is the country with the largest per capita number of refugees in the world. In addition, the country experienced a social, economic, and political crisis in 2019 that destabilized the entire society-circumstances that were further complicated by COVID-19 pandemic. With all of the competing calamities in Lebanon, there has been limited scientific investigation into substance use and the risk of HIV infection among the country's population. To address this gap in knowledge, a qualitative rapid situational assessment (RSA) of substance use and risk of HIV infection in and around Beirut, the nation's capital, was conducted. The goal of this analysis is to describe the demographics and drug use patterns of this population, explore their HIV knowledge and risks, and build knowledge about their perceptions of and access to substance use treatment and other social services.
0 citations (Crossref) [2023-10-31]
Keywords: COVID-19; Drug Users; HIV Infections; HIV risk; Health Services Accessibility; Humans; Lebanon; Pandemics; Refugees; Stress; Psychological; Substance-Related Disorders; dept.swk; peer-reviewed; rapid situational assessment; refugees; substance use